Co incorporated Ni3S2 hierarchical nano/micro cactus for electrochemical water splitting. (13th August 2019) - Khan, Rimpa; Samanta, Madhupriya; Ghosh, Shrabani; Das, Nirmalya Sankar; Chattopadhyay, Kalyan Kumar
Abstract: Hierarchical nano/micro Ni3 S2 cactus like structures were fabricated using cost effective and eco-friendly hydrothermal technique. Both pure and Co:Ni3 S2 composite nanostructures were grown on nickel foam under different synthesis temperatures. The synthesized nanostructures showed a wide variation of hierarchical morphology with variation of synthesis temperatures. The obtained nanostructures were investigated for electrochemical water splitting performance. The morphologies of the samples were found to acquire higher aspect ratio with increment in synthesis temperature. This morphological tuning led to remarkable enhancement in hydrogen evolution performance with very low overpotential 206 mV at 100 mA cm −2 in acidic medium. Owing to this superior morphology tuned water splitting performance, this low dimensional Ni3 S2 system can be recognized as potential leader in electrochemical energy harvesting sector. Highlights: Co doped Ni3 S2 hierarchical nanostructures were synthesized for the first time. Morphological tuning was successfully correlated with synthesis temperature. High aspect ratio was identified as key factor for better electrochemical property. Highly efficient hydrogen evolution with very low overpotential of 206 mV.